NEUROPSYCHOLOGICAL IMPAIRMENTS IN ADULT CHRONIC HYDROCEPHALUS: DEFINITION AND SOME SUGGESTIONS FOR ASSESSMENT - Matarín Jiménez, María del Mar; Mataró, María; Poca, Maria Antonia (Anales de Psicología / Annals of Psychology, 2004)
Normal pressure hydrocephalus or adult chronic hydrocephalus (ACH) was first characterized in 1965 by Hakim and Adams as a condition with ventricular dilation accompanied by a progressive clinical triad of gait disturbance, “dementia” and incontinente. Patients with ACH syndrome present a fronto-subcortical type of cognitive dysfunction. Evidence of cortical dysfunction in the ACH syndrome suggests the presence of a concomitant cause of dementia. This possible association explains the wide variation in the severity and type of cognitive deficits presented by ACH patients before and after shunting. Dementia in ACH can be partially or completely reversed with treatment. However, there is a great heterogeneity in the treatment results which has been mainly attributed to patient selection criteria. For this reason and the potential risks of the treatment, many studies are trying to find or improve the diagnostic techniques in ACH. This paper reviews research work centered on neuropsychological impairment and diagnostic methods in patients with ACH syndrome.